ANTICIPATION OF EDUCATIONAL SYSTEMATICS CHANGES DURING AND AFTER THE COVID-19 PANDEMIC: A GOVERNMENTAL LEGITIMACY - Elvrida N. Sinaga (Scientium Educational Review, 2022)
The COVID-19 pandemic since the beginning of 2020 has affected education systems and management throughout Indonesia, such as teaching and learning activities in an online system, increasing stress and boredom, and causing anxiety and depression for students. The government has made various efforts to address the existing obstacles. However, these efforts have not been able to overcome prolonged negative impacts, such as the threat of dropping out of school, students having to work to help family finances due to the COVID-19 pandemic crisis, the occurrence of learning achievement gaps due to differences in access and quality, the occurrence of covert exploitation of children, and the tendency to students become addicted to online games. This study uses a qualitative approach with library studies using legitimacy theory to answer these existing problems. Two conclusions were drawn; first, the education system before the COVID-19 pandemic was still based on formal, non-formal, and informal education, which was held in an open system through face-to-face and or long-distance. Second, the anticipation of systematic changes in education during and after the COVID-19 pandemic to create advanced, trustworthy, and dignified graduates is carried out by implementing legitimacy theory by integrating technology, information, and communication with business process reengineering (BPR).